(untitled) (Journal of actual problems of jurisprudence, 2019)
This article deals with the role which plays an international commercial arbitration in resolving disputes arising in the sphere of foreign-economic activity. Specified legal base has been formed in Kazakhstan which provides resolving disputes by international commercial arbitration. And also legal nature of international commercial arbitration is defined here.